2011
DOI: 10.1186/1472-6750-11-33
|View full text |Cite
|
Sign up to set email alerts
|

A Sleeping Beauty DNA transposon-based genetic sensor for functional screening of vitamin D3 analogues

Abstract: BackgroundAnalogues of vitamin D3 are extensively used in the treatment of various illnesses, such as osteoporosis, inflammatory skin diseases, and cancer. Functional testing of new vitamin D3 analogues and formulations for improved systemic and topical administration is supported by sensitive screening methods that allow a comparative evaluation of drug properties. As a new tool in functional screening of vitamin D3 analogues, we describe a genomically integratable sensor for sensitive drug detection. This sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 56 publications
(59 reference statements)
2
16
0
Order By: Relevance
“…Approximately 200 000 HEK‐293 cells were seeded in six‐well plates and cultured as described above. The next day, cells were co‐transfected with pT2/CMV‐VEGF SV40‐Neo and pCMV‐SB100X , using 1 µg of each vector and FuGENE®6 (Roche) . Twenty‐four hours post‐transfection, the cells were diluted (1:10 and 1:100) and transferred to p10 Cellstar tissue culture dishes (Greiner, In Vitro AS, Fredensborg, Denmark) and incubated for 72 h. Then, media was replaced with fresh medium containing 1.5 mg/ml Neomycin (G418; Roche).…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 200 000 HEK‐293 cells were seeded in six‐well plates and cultured as described above. The next day, cells were co‐transfected with pT2/CMV‐VEGF SV40‐Neo and pCMV‐SB100X , using 1 µg of each vector and FuGENE®6 (Roche) . Twenty‐four hours post‐transfection, the cells were diluted (1:10 and 1:100) and transferred to p10 Cellstar tissue culture dishes (Greiner, In Vitro AS, Fredensborg, Denmark) and incubated for 72 h. Then, media was replaced with fresh medium containing 1.5 mg/ml Neomycin (G418; Roche).…”
Section: Methodsmentioning
confidence: 99%
“…In cells that were cotransduced with LV/ Gal4hVDR and LV/UAS-TK-Fluc, the luminescence increased 45-fold (P < 0.001) relative to the background level upon exposure to EB1213. Importantly, we have previously shown that the sensor readout is unaffected by the presence of unligated Gal4hVDR (20). Hence, these results demonstrate tight inducibility of the dual-LV sensor system and suggest that drug-dependent transactivation of Fluc expression is achieved by a 'double-hit' of the target cells with LVs carrying the essentials of the genetic sensor.…”
Section: Resultsmentioning
confidence: 73%
“…Notably, longer-lasting effects of vitamin D3 analogues, as shown here for EB1213, may help to reduce dosages or the number of administrations. Indeed, EB1213 exhibits anti-proliferative and differentiation-promoting properties at lower concentrations than other vitamin D3 analogues including calcipotriol (20,38,43,45). In summary, our findings underline the potential of an in vivo sensor system as a quantitative screening methodology in the pursuit of novel, therapeutically attractive vitamin D3 analogues.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Recently, Staunstrup et al ( 2011 ) used a genomically integratable transposon system for the assessment of the pharmacokinetic and pharmadynamic properties of vitamin D3 analogues (Staunstrup et al 2011 ) . A tri-cistronic Sleeping beauty transposon was cloned from which three different proteins are encoded: a drug-sensoring protein, a reporter protein expressed from an activated sensor-responsive promoter and a resistance marker allowing clonal selection.…”
Section: Drug Discoverymentioning
confidence: 99%